The effect of physical exercise on sleep quality in university students: chain mediation of health literacy and life satisfaction - He, Mo-Han; Zhao, Tian-Yu; Zhu, Wei-Dong; Lou, Hu; Zhang, Ding-You; Mu, Fan-Zheng; Zhang, Xin-Yu; Li, Yu-Han; Zhang, Wen-Hao; Liu, Qi; Wang, Jia-Qiang; Li, Chen-Xi; et al. (Frontiers in Psychology, 2025)
ObjectiveThe present study was designed to explore the relationship between physical exercise and sleep quality. Specifically, it investigates the extent to which this relationship is mediated by a sequential process involving health literacy and life satisfaction.MethodsData on physical exercise, sleep quality, health literacy, and life satisfaction were collected from a sample of 12,646 college students (study participants) using a questionnaire. Statistical analyses were performed using SPSS and AMOS software, including descriptive statistics, correlation analysis, and regression analysis.ResultsCorrelation analyses revealed a weak positive correlation between physical exercise and sleep quality (r = 0.290), a significant positive correlation between physical exercise and health literacy (r = 0.203, p < 0.01), and a significant positive correlation between physical exercise and life satisfaction (r = 0.374, p < 0.01). Conversely, sleep quality exhibited a significant negative correlation with health literacy (r = −0.091, p < 0.01) and a significant negative correlation with life satisfaction (r = −0.228, p < 0.01). Health literacy and life satisfaction were significantly positively correlated (r = 0.352, p < 0.01). Regression analysis indicated that physical exercise did not directly and significantly predict sleep quality (β = −0.010). This study exhibits a complete mediation effect. However, mediation analysis revealed a significant indirect effect of physical exercise on sleep quality through health literacy (95% CI: [−0.022, −0.013]) and life satisfaction (95% CI: [−0.024, −0.015]). Furthermore, a significant chain-mediating effect was observed, wherein physical exercise influenced sleep quality sequentially through health literacy and life satisfaction (95% CI: [−0.018, −0.013]). The non-significant direct effect of physical exercise on sleep quality and the significant indirect impact suggest that the relationship between physical exercise and sleep quality is primarily mediated through health literacy and life satisfaction. These findings highlight the crucial role of health literacy and life satisfaction as mediators in this relationship.ConclusionWhile physical exercise did not exert a direct and significant effect on sleep quality in this study, the significant mediating roles of health literacy and life satisfaction suggest potential avenues for intervention. Specifically, these findings imply that multifaceted approaches, encompassing strategies to promote physical activity, enhance health literacy, and improve life satisfaction, may improve sleep quality among college students.